Behavior of GFRP bridge deck panels infilled with polyurethane foam under various environmental exposure. (February 2016) - Tuwair, Hesham; Volz, Jeffery; ElGawady, Mohamed; Mohamed, Mohaned; Chandrashekhara, K.; Birman, Victor
Abstract: This paper investigates the performance of polyurethane foam-infill bridge deck panels (PU sandwich panels) after being exposed to various environmental conditions. These panels were constructed with woven E-glass fiber/polyurethane facesheets that were separated by a trapezoidal-shaped, low-density polyurethane foam. Corrugated web layers were introduced into the core to enhance the panel's structural characteristics. The PU panels were manufactured through a one-step vacuum assisted resin transfer molding (VARTM) process. An experimental program was designed to simulate their in situ environments. The environmental conditions used included different conditioning regimens to examine the behavior of both GFRP laminates and PU sandwich panels. The GFRP laminates, which were made from the same materials as the PU sandwich panels, were exposed to ultraviolet radiation, a deicing solution at both room temperature and elevated temperature, and thermal cycling. The PU sandwich panels were exposed to thermal cycling (a series of freeze–thaw, mid–high temperatures, and mid–high relative humidity cycles). The thermal cycling exposure was conducted in a computer-controlled environmental chamber to duplicate seasonal effects in Midwestern states. Following the exposure regimens, tensile strength tests and four-point loading tests were performed on the GFRP laminates and the PU sandwich panels, respectively. The evaluation was based on visual inspection, strength, stiffness, and failure modes, as compared to those that were not conditioned (the control). The results of this study revealed that degradation did exist due to the effects of thermal cycling and the deicing solution. The ultraviolet radiation, however, did not cause any degradation. These results were within the recommended environmental durability design factors of the FHWA guidelines.